In Situ Hydrogen Evolution Monitoring During the Electrochemical Formation and Cycling of Pressed‐Plate Carbonyl Iron Electrodes in Alkaline Electrolyte. Issue 5 (6th April 2022) - Weinrich, Henning; Pleie, Jan; Schmid, Bernhard; Tempel, Hermann; Kungl, Hans; Eichel, Rüdiger‐A.
Abstract: Invited for this month's cover picture is the institute of Rüdiger‐A. Eichel. The cover picture illustrates the hydrogen evolution on carbonyl iron electrodes, with the latter being a resource‐efficient option to store renewable electricity for stationary applications effectively, if an appropriate charging protocol is applied. Read the full text of the Research Article at 10.1002/batt.202100415 . Abstract : "In our study, we investigated the hydrogen evolution reaction (HER) on a carbonyl iron electrode, elucidating the correlation between the applied electrode potential and the resulting rate of H2 evolution quantified by gas chromatography. Based on this analysis, we were able to show that the HER follows a distinct profile, which can be used to increase the charging efficiency of the electrode by a constant current/constant potential charging procedure. Applying this procedure led to an improved charging efficiency of 96.7%, which is a significant step towards the efficient storage of renewable electricity in stationary iron‐air batteries…" Learn more about the story behind the research featured on the front cover in this issue's Cover Profile. Read the corresponding Research Article on 10.1002/batt.202100415 .